Development Of Historical Map Using Padlet To Improve Students' Chronological Thinking Skills - Sinaga, Rosmaida; Sumanti, Solihah Titin; Nababan, Surya Aymanda; Soriente, Antonia; Mulyani, Fini Fajri (JETL (Journal of Education, Teaching and Learning), 2024)
This research aims to develop Historical Map media to improve students' chronological thinking skills. This research uses an R&D method which consists of four stages, namely. The research subjects consisted offrom 6 experts, 2 teachers, and 150 class students XI provided an assessment related to the media being developed. The collected data was analyzed through validity, reliability, T test and N-Gain tests. The research results show that the Historical Map media obtained a validation score of 3.65. Meanwhile, the practicality score for the Historical Map media obtained a score of 4.01, which indicates that the media developed can be easily implemented in history learning. The T test obtained a score of 0.000, which shows that there is an influence of using Historical Map media on students' chronological thinking skills. The results of the N-Gain Test indicate that the influence of using Historical Map media on students' chronological thinking skills increased by around 69%. Therefore, it can be concluded that the development of Historical Map media to improve students' chronological thinking skills has proven to be valid, reliable, practical and effective.